2019
DOI: 10.1096/fj.201900730r
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate–induced TNF‐α is regulated by crosstalk between the aryl hydrocarbon receptor, NF‐κB, and SOCS2 in human macrophages

Abstract: Indoxyl sulfate (IS) is a uremic toxin associated with increased prevalence of cardiovascular diseases (CVDs) in patients with chronic kidney disease. Despite the crucial role of uremia‐related immune dysfunction, a majority of studies attempting to elucidate its pathogenic role in CVD have focused on IS‐mediated endothelial dysfunction. Thus, we investigated the underlying molecular mechanisms involved in IS‐induced production of TNF‐α, a major cardiotoxic cytokine, by human macrophages. We found that crossta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 64 publications
(104 reference statements)
1
35
0
Order By: Relevance
“…A previous study also reported that AhR was ubiquitinated and degraded by the proteasome system after binding to its ligand [24]. It has recently been reported that IS is an endogenous agonist of AhR [25][26][27][28]. AhR is a ligand-activated transcription factor involved in the biological detoxification of ligands [29].…”
Section: Discussionmentioning
confidence: 96%
“…A previous study also reported that AhR was ubiquitinated and degraded by the proteasome system after binding to its ligand [24]. It has recently been reported that IS is an endogenous agonist of AhR [25][26][27][28]. AhR is a ligand-activated transcription factor involved in the biological detoxification of ligands [29].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, IxS induces monocytic ROS production in an NADPH oxidase-dependent manner [82]. The IxS-induced TNF-α production in macrophages is regulated through a mechanism involving the interaction of AhR, NF-κB, and the suppression of cytokine signaling [83]. IxS also increases LPS-induced NF-κB nuclear translocation, ROS release and altered calcium concentrations in J774A.1 macrophages, mainly because of mitochondrial calcium overloading [84].…”
Section: Indoxyl Sulfatementioning
confidence: 99%
“…Functional GSEA of monocytes from patients with ESRD identified the alteration of major metabolic pathways including glycolysis, oxidative phosphorylation, and fatty acid metabolism, as well as immune response-related pathways such as interferon-α and γ responses, the inflammatory response, and TNF-α signaling via NF-κB ( Figure 3 and Table S3 ). We and others have demonstrated that IS elicits immune responses by its binding to AhR in monocytes/macrophages [ 36 , 37 ]. Thus, identification of immune response-related pathways in GSEA was expected.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is also considered an important pro-atherogenic cytokine in CVD [ 47 ]. In addition, IS is a potent endogenous ligand for AhR, and IS-stimulation of monocytes/macrophages results in increased production of TNF-α through a complicated regulation mechanism between AhR, NF-κB, and SOCS2 [ 16 , 36 ]. Chemokines and their receptors regulate migration of leukocytes under normal and inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%